Effects of pre- and post-fermentative practices on oligomeric cyclic and non-cyclic condensed tannins in wine from Schiava grapes - Aakriti Darnal; Simone Poggesi; Adriana Teresa Ceci; Tanja Mimmo; Emanuele Boselli; Edoardo Longo (Current Research in Food Science, 2023)
The effects of a) pre-fermentative freezing of the grapes (- 20 °C for two weeks); b) inoculation of the grape must with Saccharomyces cerevisiae yeast, or co-inoculation with Saccharomyces cerevisiae yeast and Oenococcus oeni bacteria; c) vinification with or without fermentative maceration, and d) cold stabilization with or without bentonite treatment, were studied on the profile of oligomeric condensed tannins (proanthocyanidins, PAC) with non-cyclic or macrocyclic structures in wines made from Schiava cv., a red grape variety. The samples were evaluated just before inoculation and at the bottling of the wine. Commercial Schiava wines from two different producers stored at six and eighteen months were also studied for the effect of artificially introduced dissolved oxygen, and half of these bottles were subjected to periodic mechanical stress for one year, to see the effects on the PAC profile. Freezing of the grapes increased the extraction of all non-cyclic PAC in the must, whereas tetrameric, pentameric, and hexameric cyclic procyanidins (m/z 1153, m/z 1441, m/z 1729, respectively) were not affected; only a tetrameric cyclic prodelphinidin ( m/z 1169) showed a more similar trend to the non-cyclic PAC. In wines at bottling, cyclic procyanidins were higher in wines obtained by fermentative maceration (as well as most non-cyclic congeners); however, the significance of these differences depended on specific interactions between the factors. In contrast, no effect was found on the cyclic tetrameric prodelphinidin (m/z 1169). Bentonite treatment showed no significant effect on either oligomeric non-cyclic or cyclic PAC profiles. The addition of dissolved oxygen led to a significant decrease in non-cyclic trimeric and tetrameric PAC in the samples with respect to the control ones; however, the addition of dissolved oxygen did not influence the profile of the cyclic PAC. This study sheds new light on the substantial differences in the behaviour of the cyclic and non-cyclic oligomeric PAC in red wine in relation to the vinification process and in the bottle. Cyclic oligomeric PAC were more stable and less influenced by applied factors than linear PAC, again proving to be potential markers for the grape variety of wine.